COVID-19 research streams emerging in International Financial Reporting Standards related studies - Santos, M. R. C.; Dias, R.; Heliodoro, P.; Alexandre, P. (Fifth International Scientific Conference ITEMA: Recent Advances in Information Technology, Tourism, Economics, Management and Agriculture. Conference Proceedings, 2021)
Interpretation for the adoption of the International Financial Reporting Standards (IFRS) became to be challenging for organizations. Over time, these standards are changed to accommodate the improvements identified in accounting rules. COVID-19 pandemic impacted accounting reporting considering that contingencies and risks arising from this health crisis should be reported to stakeholders. In order to provide empirical evidence of the most important COVID-19 related practical and academic issues and challenges addressed by academics when reporting under IFRS, this study applies an automated computer-aided analysis for clustering the bibliometric data published concerning IFRS and COVID-19. The results support academic studies and practitioners by identifying the COVID-19 research streams that received the most attention in 2020. This study also suggests guidelines for future research that derive from past academic contributions.